Pengaruh Pendampingan Masyarakat dalam Pemilahan Sampah di Desa Pucung Kecamatan Tirto Kabupaten Pekalongan - Samadikun, Budi Prasetyo (Universitas Diponegoro, 2018)
Potential problems in household waste management are still found, especially in residential areas. Pucung Village, Tirto District Pekalongan Regency with a population of 3.347 people, is one example of a village that has not implemented waste management properly. The availability of inadequate trash can be one of the factors that causes the waste has not been well managed in this village. This community assistance activity aims to educate and encourage the community to be self-sufficient in waste management, especially in waste sorting. According to the recommendations of Pucung Village Government, this community assistance activity is centered in RT 04 RW 01 area as an embryo or pilot project to be implemented in all Pucung Village area. The methods used are survey, socialization, simulation, and post-socialization follow-up. The residents are quite enthusiastic and appreciative towards this activity, shown by the attendance rate of more than 60% during socialization and conducive discussion. The results of post-socialization evaluation indicate that people have started to realize in managing waste, indicated by the separated garbage in a different trash can at their residenceKeywords:Â accompaniment, sorting, waste, Pucung